Frontline Science: Rev-Erbα links blue light with enhanced bacterial clearance and improved survival in murine Klebsiella pneumoniae pneumonia. Issue 1 (4th August 2019) - Griepentrog, John E.; Zhang, Xianghong; Lewis, Anthony J.; Gianfrate, Gianmarino; Labiner, Hanna E.; Zou, Baobo; Xiong, Zeyu; Lee, Janet S.; Rosengart, Matthew R.
Abstract: The wavelength of light is a critical determinant of light's capacity to entrain adaptive biological mechanisms, such as enhanced immune surveillance, that precede and prepare us for the active circadian day, a time when the risk of encountering pathogen is highest. Light rich in the shorter wavelength visible blue spectrum maximally entrains these circadian rhythms. We hypothesized that exposure to blue light during sepsis will augment immunity and improve outcome. Using a clinically relevant Klebsiella pneumoniae acute lower respiratory tract infection model, we show that blue spectrum light shifts autonomic tone toward parasympathetic predominance and enhances immune competence, as characterized by accelerated pathogen clearance that is accompanied by reduced alveolar neutrophil influx, inflammation, and improved survival. Blue light functioned through an optic-cholinergic pathway and expansion of splenic Ccr2 + monocytes to increase control of the infection and improve survival. The "keystone" mediating these effects is the circadian clock protein Rev-Erbα, and biochemical activation with Rev-Erbα agonist SR9009 enhanced mononuclear cell phagocytosis in vitro and recapitulated the enhanced pathogen elimination in vivo observed with blue light. These findings underscore the potential therapeutic value of blue light and modulating Rev-Erbα to enhance host immunity against infection.